INSIGHTS INTO RESEARCH ON THE ANTI-INFLAMMATORY AND ANTINOCICEPTIVE ACTIVITIES OF SCANDIX IBERICA BIEB - Guragac, Fatma Tugce; Ilhan, Mert; Tumen, Ibrahim; Akkol, Esra Kupeli (Parlar Scientific Publications (P S P), 2017)
It is thought that bioactive compounds from plant foods may have beneficial health effects and decrease the risk of chronic inflammatory diseases. In Turkish folk medicine, flowers of the Scandix iberica Bieb. (Apiaceae) have been used to combat rheumatic pain. The aim of this study is to appraise the anti-inflammatory and antinociceptive activities of the different types of extracts prepared from S. iberica carrageenan, Prostaglandin E2 (PGE2) and serotonin-induced hind-paw oedema, acetic acid-induced capillary permeability and 12-O-tetradecanoyl-phorbol-13-acetate (TPA)-induced mouse-ear oedema models were used to appraise anti-inflammatory activity. Antinociceptive activity was tested using a p-benzoquinone induced abdominal constriction method. Among the extracts, only the n-Hexane extract was shown to possess a noticeable anti-inflammatory and antinociceptive activity in mice without inducing any gastric damage at 100 and 200 mg/kg doses, while the rest of the extracts were entirely inactive. The activity of the n-Hexane extract led to a greater appreciation of some phenylpropanoids, mainly estragole (88.90 %), through Capillary Gas chromatography-Mass Spectrometry (GC-MS).
Keywords: Scandix Iberica; Apiaceae; Estragole; Anti-Inflammatory Activity; Antinociceptive